Process design method for improving strength and plasticity of Al-Mg-Si alloy

By establishing a thermal-kinetic model during the unequal solidification process of Al-Mg-Si alloy, studying the solidification behavior under cold speed conditions, the microstructure control problem in strong plastic processing of aluminum alloy is solved, and the mechanical properties of the alloy are improved , provides new material research and development ideas.

CN119150554APending Publication Date: 2024-12-17NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411264695.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art lacks effective process design methods in the strong plastic processing of aluminum alloys, making it difficult to deeply understand and control the microstructure evolution of aluminum alloys during solidification and heat treatment, affecting the mechanical properties of the final molded parts.

Method used

During the unequal solidification process of Al-Mg-Si alloy, a thermal-kinetic model is established, the solidification behavior under different cold speed conditions is studied, the number density and growth process of nano Si are calculated, and the phase change energy barrier and interface migration are obtained. The rate, and then the optimal cooling rate is selected to improve the strong plasticity of the alloy.

Benefits of technology

The improvement of the mechanical properties of Al-Mg-Si alloys has been achieved, revealing the correlation between thermodynamic driving force and dynamic energy barrier, and providing new material research and development ideas. By selecting the phase change path of large driving force and large energy barrier, Obtain better mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119150554A_ABST
    Figure CN119150554A_ABST
Patent Text Reader

Abstract

The invention discloses a process design method for improving the strength and plasticity of an Al-Mg-Si alloy, and relates to the technical field of aluminum alloy processing. According to the method, the relation between the generalized stability of solidification and the driving force and the phase change energy barrier of precipitation phase precipitation is established based on the thermo-dynamics of the Al-Mg-Si alloy in the non-equilibrium solidification process; acquiring the interface migration rate between the Si and the aluminum matrix of the samples with different cooling rates; the driving force for precipitation of the precipitation phase is obtained according to the liquid phase solute components; a phase change energy barrier is obtained according to the driving force for precipitation of the precipitation phase and the interface migration rate; and the cooling speed for improving the strong plasticity of the Al-Mg-Si alloy is selected according to the generalized stability. According to the method, through a generalized stability method, the structure and performance of the alloy are predicted, the relation of components / process-structure-performance is explored, and the optimal process path is selected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy processing, and in particular to a process design method for improving the strength and plasticity of an Al-Mg-Si alloy. Background Art

[0002] Al-Mg-Si alloys are widely used in the development of large aircraft in my country due to their excellent performance. During the solidification and heat treatment process, aluminum alloys will undergo complex physical processes such as solidification and solid-state phase transformation. The evolution of their microstructure will greatly affect the mechanical properties of the final formed parts. In-depth understanding of the phase transformation process and effective control of the organizational evolution during the processing of aluminum alloys are important issues in significantly improving the performance of aluminum alloys.

[0003] Today, the method for strengthening metal materials is still mainly based on the traditional trial and error method. Realizing the rational design of advanced metal structural materials and clarifying the closed-loop relationship of "composition-structure-process-performance" are the primary prerequisites for breaking the traditional R&D trial and error model. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned background technology, the present invention provides a process design method for improving the strength and plasticity of Al-Mg-Si alloy, so as to improve and control the heat treatment process of Al-Mg-Si aluminum alloy and achieve the purpose of improving both strength and plasticity.

[0005] The first object of the present invention is to provide a process design method for improving the strength and plasticity of Al-Mg-Si alloy, comprising: Based on the thermodynamics of Al-Mg-Si alloy in nonequilibrium solidification process, the relationship between the generalized stability of solidification and the driving force of precipitation and phase transformation energy barrier is established. Select TCAL5 and MOBAL4 data packages to obtain the liquid solute composition and the fraction of the formed solid phase under different cooling rate conditions according to the Scheil equation; The number density of nano-Si at different cooling rates was obtained according to the fraction of solid phase formed under different cooling rates. According to the number density of nano-Si at different cooling rates, the thermodynamic calculation of the nano-Si growth process was performed to obtain the interface migration rate between Si and aluminum matrix of samples with different cooling rates. Obtain the driving force for precipitation of the precipitate phase based on the liquid phase solute composition; The phase transition energy barrier is obtained based on the driving force of precipitation phase and interface migration rate; According to the driving force and energy barrier of precipitation phase, the generalized stability is obtained based on the relationship between the generalized stability and the driving force and energy barrier of precipitation phase. The cooling rate for improving the strength and ductility of Al-Mg-Si alloy is selected based on the generalized stability.

[0006] Preferably, the relationship between the generalized stability and the driving force for precipitation of the precipitated phase and the phase transition energy barrier is as follows:

[0007] In the formula, represents generalized stability; represents the phase transition energy barrier; It represents the driving force for the precipitation of the precipitate phase; It represents the chemical driving force of the initial phase transition at constant cooling rate; Represents the energy barrier of the initial state of phase transformation at constant cooling rate.

[0008] Preferably, the liquid phase solute component is calculated by the following formula:

[0009] In the formula, Indicates the nominal composition of the alloy; is the equilibrium distribution coefficient of the solute at the solid-liquid interface; It is the solid phase solute component; is the solid phase fraction.

[0010] Preferably, the fraction of the formed solid phase is calculated as follows:

[0011] In the formula, represents the transition temperature; represents absolute temperature; represents the liquidus temperature; is the equilibrium distribution coefficient of the solute at the solid-liquid interface.

[0012] Preferably, the driving force for the precipitation of the precipitated phase is calculated as follows:

[0013] In the formula, is the Boltzmann constant; T is temperature; For the atomic body; It is the liquid phase solute component; is the equilibrium concentration of solute atoms in the matrix.

[0014] Preferably, the phase change energy barrier is calculated as follows:

[0015] In the formula, It represents the driving force for the precipitation of the precipitate phase; represents the interface migration rate; is the pre-exponential factor; is the gas constant; is the absolute temperature.

[0016] Preferably, the Aziz solute retention model in the non-equilibrium solidification process is as follows:

[0017]

[0018] In the formula, is the solute retention function; is the interface migration rate; is the solute diffusion rate; is the equilibrium segregation coefficient ratio of solute component A and solvent component B; is the liquid fraction on the moving interface; is the speed of sound in the metal melt; It is the driving force during the solidification of the alloy; is the gas constant; is the interface temperature.

[0019] The second object of the present invention is to provide an application of the above method in improving the strength and plasticity of Al-Mg-Si alloy.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a process design method for improving the strength and plasticity of Al-Mg-Si alloy. The present invention takes Al-Mg-Si alloy as the research object, studies the organizational evolution law under different non-equilibrium solidification conditions and different aging times, improves the mechanical properties of aluminum alloy, and reveals the correlation between thermodynamic driving force and dynamic energy barrier. Through the generalized stability method, the organization and performance of the alloy are predicted, the relationship between composition / process-organization-performance is explored, and the best process path is selected.

[0021] The non-equilibrium solidification structure and mechanical properties in the present invention are linked to the thermodynamic calculation results of the phase change process, realizing the correlation between driving force, generalized stability, and structure and mechanical properties. That is, the greater the driving force at the final state of the phase change, the higher the corresponding strength; the greater the generalized stability at the final state of the phase change, the better the corresponding plasticity. This provides a new idea for material research and development, that is, by selecting a phase change path with a large driving force, a large energy barrier, and a large generalized stability, the material can obtain better mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the content change of Si element in FCC phase during the solidification process of Al-Mg-Si alloy; Figure 2 This is the graph showing the change of the number density of nano-Si with temperature during the cooling process of Al-Mg-Si alloy; Figure 3 is the change of interface migration rate with temperature during cooling; Figure 4 The thermodynamic driving force and kinetic energy barrier of nano-Si precipitation during the cooling process of Al-Mg-Si alloy vary with temperature: (a) 1.5K / S; (b) 10K / S; (c) 20K / S; (d) 120K / S; Figure 5 The driving force and energy barrier of the final state of the Al-Mg-Si alloy reaction are related to the cooling rate; Figure 6 The generalized stability of Al-Mg-Si alloy varies with temperature at different cooling rates; Figure 7 Microstructural characteristics of A356 alloy at different cooling rates: (a) 1.5K / s; (b) 10K / s; (c) 20K / s; (d) 120K / s; Figure 8 Engineering stress-strain curves of the alloy at different solidification cooling rates. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0024] The invention discloses a process design method for improving the strength and plasticity of Al-Mg-Si alloy, which is used to improve and control the heat treatment process of Al-Mg-Si aluminum alloy and achieve the purpose of improving the strength and plasticity at the same time.

[0025] Example 1 A process design method for improving the strength and plasticity of Al-Mg-Si alloy, comprising: S1. Based on the thermodynamics of Al-Mg-Si alloy in the non-equilibrium solidification process, the relationship between the generalized stability of solidification and the driving force of precipitation and phase transformation energy barrier is established; The relationship between the generalized stability and the driving force for precipitation of the precipitated phase and the phase transition energy barrier is as follows:

[0026] In the formula, represents generalized stability; represents the phase transition energy barrier; It represents the driving force for the precipitation of the precipitate phase; It represents the chemical driving force of the initial phase transition at constant cooling rate; Represents the energy barrier of the initial state of phase transformation at constant cooling rate.

[0027] S2, select TCAL5 and MOBAL4 data packages, and obtain the liquid solute composition and the fraction of the formed solid phase under different cooling rate conditions according to the Scheil equation; The liquid phase solute component is calculated by the following formula:

[0028] In the formula, Indicates the nominal composition of the alloy; is the equilibrium distribution coefficient of the solute at the solid-liquid interface; It is the solid phase solute component; is the solid phase fraction.

[0029] The fraction of the formed solid phase is calculated as follows:

[0030] In the formula, represents the transition temperature; represents absolute temperature; Indicates the liquidus temperature.

[0031] is the equilibrium distribution coefficient of the solute at the solid-liquid interface.

[0032] The Aziz solute retention model in the nonequilibrium solidification process is as follows:

[0033]

[0034] In the formula, is the solute retention function; is the interface migration rate; is the solute diffusion rate; is the equilibrium segregation coefficient ratio of solute component A and solvent component B; is the liquid fraction on the moving interface; is the speed of sound in the metal melt; It is the driving force during the solidification of the alloy; is the gas constant; is the interface temperature.

[0035] S3. Obtain the number density of nano-Si at different cooling rates according to the fraction of solid phase formed under different cooling rates; S4. According to the number density of nano-Si at different cooling rates, thermodynamic calculation is performed on the growth process of nano-Si to obtain the interface migration rate between Si and aluminum matrix of samples with different cooling rates; S5. Obtaining the driving force for precipitation of the precipitate phase according to the solute composition of the liquid phase; The phase transition energy barrier is obtained based on the driving force of precipitation phase and interface migration rate; The driving force for the precipitation of the precipitated phase is calculated as follows:

[0036] In the formula, is the Boltzmann constant; T is temperature; For the atomic body; It is the liquid phase solute component; is the equilibrium concentration of solute atoms in the matrix.

[0037] The phase change energy barrier is calculated as follows:

[0038] In the formula, It represents the driving force for the precipitation of the precipitate phase; represents the interface migration rate; is the pre-exponential factor; is the gas constant; is the absolute temperature.

[0039] S6. Obtaining generalized stability based on the driving force and energy barrier for precipitation of the precipitate phase and the relationship between generalized stability and the driving force and energy barrier for precipitation of the precipitate phase; The cooling rate for improving the strength and ductility of Al-Mg-Si alloy is selected based on the generalized stability.

[0040] The present invention provides an application of the above method in improving the strength and plasticity of Al-Mg-Si alloy.

[0041] Example 2 A process design method for improving the strength and plasticity of Al-Mg-Si alloy, the steps are as follows: Step 1: Solve the driving force and generalized stability in the solidification process: establish a generalized stability applicable to solidification based on the thermodynamics of the solidification process, and solve the driving force and generalized stability of the solidification process; When a phase transition occurs, the strain energy and interface energy of the new phase will try to inhibit the occurrence of the phase transition, thus forming a critical state. When the driving force is greater than the resistance, the new phase continues to nucleate and grow. As the initial stage of phase transition, nucleation usually overlaps with subsequent growth (i.e., interface migration) and is accompanied by solute or heat diffusion.

[0042] (1) In the formula The chemical driving force, is the strain energy, is the interface energy.

[0043] There are two types of phase transitions. When the interfacial energy approaches 0, what is needed is a slight fluctuation of the solute atomic groups within the overall range, that is, structural fluctuation or composition fluctuation. The phase transition that occurs at this time is an overall uniform phase transition, a uniform nucleation + growth situation; when the interfacial energy exists in the parent phase, what is needed is a drastic fluctuation of the solute elements or structure within the local range. The phase transition at this time is an inhomogeneous phase transition or a discontinuous phase transition. According to the size of the interfacial energy (strain energy) and the molar volume chemical free energy, the critical nucleus size and critical nucleation work can be determined: (2) (3) In the formula is the free energy per unit area, is the difference between unit volume and unit Gibbs free energy.

[0044] The Gibbs energy of the molar chemical change ( ) and the strain energy associated with the volume mismatch between the new phase and the parent phase ( ) two aspects of contribution. The magnitude of the driving force depends on the conversion process and increases with the increase of the phase transformation fraction (f) after the conversion, and approximately follows a linear relationship. Therefore, by taking a linear approximation, we obtain equation (4). At the same time, the classical nucleation theory shows that the nucleation activation energy includes the critical nucleation work and the interface migration activation energy ( ), the total effective energy barrier accompanying the growth should be the growth of the nucleated part ( ) and the nucleation of the unnucleated part.

[0045] (4) (5) For a phase transition with a gradually increasing energy barrier and a gradually decreasing power, whether it is an isothermal or constant heating rate transition, equations (4) and (5) can be written as: (6) (7) According to the concept of generalized stability: Combining equation (6) with equation (7), we can get: (8) Considering that thermal stability is contributed by both thermodynamics and kinetics, by transforming equation (8), the generalized stability GS can be defined as: (9) The above derivation is strictly applicable to isothermal phase transition, remains unchanged. For the transition with constant cooling rate, the supercooling degree of nucleation gradually increases, the driving force becomes larger and larger, the critical size gradually decreases, and the critical nucleation work also gradually decreases; under the premise of heterogeneous nucleation assumption, assuming that the entire cooling consists of multiple isothermal micro-stages, then, according to isokinetics, the overall cooling process can be approximated as the transition of the energy barrier from volume diffusion to interface migration according to the change of driving force from small to large. Equation (7) is modified as follows: (10) get: (11) According to the second law of thermodynamics and the isokinetic hypothesis, we can always find an isothermal transformation at a certain temperature (between the reference temperature and the end point of the phase change) to replace the constant cooling rate transformation. Using the same derivation method at this temperature, formula (11) can be expressed as: (12) In the formula, and Compared with formula (11) and are larger and smaller respectively, and the difference between them can be considered negligible. Defined as the chemical driving force for the initial phase transition at constant cooling rate, Defined as the energy barrier to the initial state of phase transformation at constant cooling rate.

[0046] It can be understood that for a given phase transition, the interface migration activation energy, the bulk diffusion activation energy, and the overall strain energy are all given, and the quantitative reduction of the chemical driving force during the phase transition is reflected in the quantitative increase of the kinetic energy barrier.

[0047] Step 2: Thermodynamic calculation of aluminum solidification process: According to the lever rule, the liquid phase solute composition can be expressed as: (13) In the formula is the nominal alloy composition, is the equilibrium distribution coefficient of the solute at the solid-liquid interface, is the solid phase solute component, is the solid phase fraction; Although the lever law is simple in form, the equilibrium solidification it describes is extremely difficult to achieve, and the actual solidification process is basically non-equilibrium solidification. Another simple microsegregation model corresponding to the lever law is the Gulliver-Scheil model (abbreviated as the Scheil equation) that takes non-equilibrium solidification into account. According to the Scheil equation, the liquid solute composition can be expressed as: (14) Fraction of solid phase formed: (15) The Scheil calculator in Thermo-Calc is used to simulate the solidification process at different cooling rates. In the Scheil module, we select the solute interception model to handle the non-equilibrium solidification process. This model is based on the Aziz solute interception model: (16) (17) In the formula is the solute retention function (kinetic segregation coefficient), is the interface moving speed, is the solute diffusion velocity, is the equilibrium segregation coefficient ratio of components A (solute) and B (solvent), is the liquid fraction on the moving interface, is the speed of sound in the metal melt, It is the driving force during the alloy solidification process. is the gas constant, is the interface temperature.

[0048] Step 3: Thermodynamic calculation of aluminum alloy solid phase transformation process: 1. Nucleation process When the cluster size is larger than the critical nucleation radius, the nucleation and growth of the new phase are promoted. This critical nucleation radius can be expressed as: (18) In the formula is the interface energy between particles and matrix.

[0049] It can be seen from formula (21) that the greater the solute concentration, the smaller the critical nucleation radius of the precipitation phase, that is, the easier it is to nucleate. The nucleation rate I can be expressed by the following formula, namely: (19) In the formula is the nucleation rate, is the number of atoms per unit volume of the parent phase, is the critical nucleation work, is the atomic diffusion activation energy, is the atomic vibration frequency, Absolute temperature 。

[0050] 2. Growth process Assuming that the supersaturated solid solution is an ideal solution, the samples with different cooling rates actually experience the same temperature range. By comparing the temperatures experienced by the samples with different cooling rates horizontally, that is, comparing the dynamics of the samples with different cooling rates at the same temperature, the driving force for the precipitation of the precipitate phase can be expressed as: (20) In the formula is the Boltzmann constant, T is the temperature, For the atomic body, is the concentration of solute atoms in the matrix, is the equilibrium concentration of solute atoms in the matrix.

[0051] Assuming that the precipitate phase is spherical, its growth rate can be expressed as: (twenty one) in, (twenty two) In the formula is the radius of the precipitated phase, is the critical coarsening radius, is the diffusion coefficient.

[0052] Interface migration speed ( V ) can be described as the interface mobility ( M ) and driving force ( ), that is, (twenty three) In the formula is the pre-exponential factor, is the gas constant, is the absolute temperature.

[0053] So as long as the driving force is given and interface migration rate The energy barrier can be obtained by : (twenty four) Get the drive Energy Barrier Then, according to formula (12), its generalized stability can be obtained, and then the experiment can be guided by the obtained generalized stability to achieve the purpose of improving both strength and plasticity.

[0054] In order to further illustrate a process design method for improving the strength and plasticity of Al-Mg-Si alloy provided by the present invention, it is further described in conjunction with the accompanying drawings.

[0055] Example 3 A process design method for improving the strength and plasticity of Al-Mg-Si alloy, comprising: The TCAL5 and MOBAL4 data packages were selected in the calculation, the FCC phase was set as the main item, the calculation was terminated at a liquid fraction of 0.04, the maximum number of iterations was 500, the accuracy was 1.0E-6, the minimum fraction was 1.0E-12, and the solidification calculation was performed at an initial temperature of 2500 K. According to the Scheil equation, the liquid solute composition can be expressed as: (1) Fraction of solid phase formed: (2) Therefore, we continue to calculate the non-equilibrium solidification process of Al-Mg-Si alloy, and quantitatively calculate the changes of Si and Mg solute element contents during solidification under different cooling rate conditions, such as Figure 1 And as shown in Table 1.

[0056] Table 1 Element contents of aluminum matrix in Al-Mg-Si alloy at different cooling rates

[0057] Figure 1 The changes in the content of Si in the matrix aluminum during the solidification process are shown. The entire solidification process of the AI-Si-Mg alloy mainly undergoes three changes: early, middle, and late stages: in the early stage of solidification, the liquid phase transforms to the FCC phase. Due to the solute capture effect, the Si element is significantly enriched in the α-A1 phase, and the element enrichment effect becomes more significant as the solidification cooling rate increases; when the temperature drops and enters the middle stage of solidification, the liquid phase transforms to the FCC phase and the diamond phase, and eutectic silicon appears in the structure. Eutectic silicon precipitates directly from the liquid phase, consuming most of the Si element in the remaining liquid phase, resulting in a significant weakening of the solute capture effect. Since the melt is in the eutectic silicon precipitation temperature range for a longer time at a low cooling rate, more eutectic silicon will be precipitated in the low cooling rate alloy compared to the high cooling rate.

[0058] In the solid-state phase change calculation, the matrix composition is based on Table 1. First, the number density of nano-Si at different cooling rates was calculated; the TC-Prisma module in the Thermo-Calc software was used for calculation, and the TCAL5 and MOBAL4 database packages were selected. The FCC phase was selected as the matrix phase, the Diamond phase was selected as the precipitation phase, and the starting temperature was 840K. Since the precipitation of nano-Si belongs to intracrystalline precipitation, the body nucleus, grain size 1.0E-4m, grain aspect ratio 1.0, and dislocation density 5.0E12m-2 were selected in the calculation. Use the software to set parameters. The precipitation number density of nano-Si at cooling rates of 1.5K / S; 10 K / s; 20 K / s: 120 K / s was calculated respectively, and the results are as follows Figure 2 shown.

[0059] like Figure 2 As shown in the figure, the number of precipitated phases in the alloy Al matrix varies with the cooling rate of the alloy, and the precipitation density of nano-Si in the matrix increases with the increase of cooling rate. The precipitation density in the samples at 1.5K / s, 10K / s, 20K / s and 120K / s is 5.08×10 21 , 9.90×10 21 , 1.40×10 22 , 1.87×10 22 Compared with the lowest cooling rate sample, the nano-Si number density of the high cooling rate sample increased by 94.9%, 176% and 268%, respectively. The high cooling rate forms a large solute element content in the matrix, which leads to a large driving force, which leads to a large nano-Si number density. The large number density will inevitably form stronger dislocation pinning in the subsequent deformation process, and ultimately make the alloy present better mechanical properties.

[0060] The Scheil calculator in Thermo-Calc is used to simulate the solidification process at different cooling rates. In the Scheil module, we select the solute interception model to handle the non-equilibrium solidification process. This model is based on the Aziz solute interception model: (3) (4) by Figure 2Based on the number density of nano-Si precipitation of samples with different cooling rates, the thermodynamic calculation of nano-Si growth process was performed through the DICTRA module in the Thermo-Calc software. The TCAL5 and MOBAL4 database packages were selected. The FCC phase was selected as the matrix phase and the Diamond phase was selected as the precipitation phase. As can be seen from Figure 2, nano-Si began to precipitate in large quantities after 350℃, so we set the starting temperature to 350℃ and the ending temperature to 30℃. The interface movement rate between Si and aluminum matrix of samples with different cooling rates is as follows: Figure 3 shown.

[0061] Assuming that the supersaturated solid solution is an ideal solution, the samples with different cooling rates actually experience the same temperature range. By comparing the temperatures experienced by the samples with different cooling rates horizontally, that is, comparing the dynamics of the samples with different cooling rates at the same temperature, the driving force for the precipitation of the precipitate phase can be expressed as: (5) In the formula is the Boltzmann constant, T is the temperature, For the atomic body, is the concentration of solute atoms in the matrix, is the equilibrium concentration of solute atoms in the matrix.

[0062] Assuming that the precipitate phase is spherical, its growth rate can be expressed as: (6) in, (7) In the formula is the radius of the precipitated phase, is the critical coarsening radius, is the diffusion coefficient.

[0063] Interface migration speed ( ) can be described as the interface mobility ( M ) and driving force ( ), that is, (8) In the formula is the pre-exponential factor, is the gas constant, is the absolute temperature.

[0064] So as long as the driving force is given and interface migration rate The energy barrier can be obtained by : (9) The driving force and energy barrier are obtained as Figure 5 As shown, The driving force and energy barrier of nano-Si precipitation in Al-Mg-Si alloy at different cooling rates were calculated. The driving force and energy barrier of the final state at each cooling rate were statistically analyzed. The results are as follows: Figure 4 As shown. With the increase of cooling rate, the driving force and energy barrier of the final state increase simultaneously, which indicates that the process of precipitation of nano-Si by non-equilibrium solidification is a phase transition process with large driving force and large energy barrier. The design strategy of large driving force-large generalized stability shows that under the premise of large driving force, there is a large energy barrier and large generalized stability. We calculated the generalized stability of nano-Si precipitation in Al-Mg-Si alloy at cooling rates of 1.5K / s, 10K / s, 20K / s and 120K / s, as shown in Figure 6 As shown in the figure, it can be seen that the generalized stability of nano-Si precipitation is between 0 and 1, and increases monotonically with decreasing temperature. The generalized stability of Al-Mg-Si alloys at 1.5K / s, 10K / s, 20K / s and 120K / s at the end is 0.48, 0.52, 0.61 and 0.76 respectively. With the increase of cooling rate, the generalized stability also increases monotonically. Generally speaking, the larger the absolute value of the generalized stability of phase transformation, the longer the phase transformation process can be, and the more persistent the phase transformation will be.

[0065] In this experiment, aluminum alloy will oxidize in the air, and direct casting may cause unnecessary obstacles to the experimental results. Therefore, before non-equilibrium solidification, the aluminum alloy ingot was first polished, and high-purity Ar gas was introduced for 15 min for melting treatment. Then 0.5 wt.% C2Cl6 was added for refining treatment in the bell jar. Finally, the slag and oxide scale of the alloy melt were removed with a skimmer, and the alloy was cast in a metal mold at 953 K. The metal mold used a self-made aluminum alloy solidification control experimental equipment, which can achieve non-equilibrium solidification within the solidification cooling rate range of 1.5 K / s-120 K / s.

[0066] Figure 7 shows the microstructure photos of A356 aluminum alloy at different solidification cooling rates. It can be seen that the solidification structure of A356 aluminum alloy is mainly composed of primary а-Al phase and lamellar eutectic Si phase distributed between dendrites. With the increase of the initial cooling rate of solidification, the secondary dendrite spacing (SDAS) of the primary а-Al phase gradually decreases. At the same time, with the increase of the initial cooling rate of solidification, the morphology of eutectic Si also evolves from coarse flakes to short rods or spheres, and the distribution of eutectic silicon is more uniform. Figure 8It is the uniaxial tensile curve of A356 aluminum alloy after cooling to room temperature at different cooling rates. The engineering stress-strain curve shows the yield strength YS (Yield Strength), ultimate tensile strength UTS (Ultimate tensile strength) and elongation at break ETF (Elongation to failure) of the material at different cooling rates. It can be seen from Table 2 that as the solidification cooling rate increases from 1.5K / s to 120K / s, the yield strength YS of the sample increases from 76MPa to 124MPa, an increase of 63%, the ultimate tensile strength UTS increases from 132MPa to 231MPa, an increase of 75%, and the elongation at break ETF increases from 6.08% to 12.94%, an increase of 113%.

[0067] Table 2 Mechanical properties of as-cast A356 aluminum alloy at different initial cooling rates during solidification

[0068] The non-equilibrium solidification structure and mechanical properties in the present invention are linked to the thermodynamic calculation results of the phase change process, realizing the correlation between driving force, generalized stability, and structure and mechanical properties. That is, the greater the driving force at the final state of the phase change, the higher the corresponding strength; the greater the generalized stability at the final state of the phase change, the better the corresponding plasticity. This provides a new idea for material research and development, that is, by selecting a phase change path with a large driving force, a large energy barrier, and a large generalized stability, the material can obtain better mechanical properties.

Claims

1. A process design method for improving the strength and plasticity of Al-Mg-Si alloy, characterized in that: include: Based on the thermodynamics of Al-Mg-Si alloy in nonequilibrium solidification process, the relationship between the generalized stability of solidification and the driving force of precipitation and phase transformation energy barrier is established. Select TCAL5 and MOBAL4 data packages to obtain the liquid solute composition and the fraction of the formed solid phase under different cooling rate conditions according to the Scheil equation; The number density of nano-Si at different cooling rates was obtained according to the fraction of solid phase formed under different cooling rates. According to the number density of nano-Si at different cooling rates, the thermodynamic calculation of the nano-Si growth process was performed to obtain the interface migration rate between Si and aluminum matrix of samples with different cooling rates. Obtain the driving force for precipitation of the precipitate phase based on the liquid phase solute composition; The phase transition energy barrier is obtained based on the driving force of precipitation phase and interface migration rate; According to the driving force and energy barrier of precipitation phase, the generalized stability is obtained based on the relationship between the generalized stability and the driving force and energy barrier of precipitation phase. The cooling rate for improving the strength and ductility of Al-Mg-Si alloy is selected based on the generalized stability.

2. The process design method for improving the strength and plasticity of Al-Mg-Si alloy according to claim 1, characterized in that: The relationship between the generalized stability and the driving force for precipitation of the precipitated phase and the phase transition energy barrier is as follows: In the formula, represents generalized stability; represents the phase transition energy barrier; It represents the driving force for the precipitation of the precipitate phase; It represents the chemical driving force of the initial phase transition at constant cooling rate; Represents the energy barrier of the initial state of phase transformation at constant cooling rate.

3. The process design method for improving the strength and plasticity of Al-Mg-Si alloy according to claim 1, characterized in that: The liquid phase solute component is calculated by the following formula: In the formula, Indicates the nominal composition of the alloy; is the equilibrium distribution coefficient of the solute at the solid-liquid interface; It is the solid phase solute component; is the solid phase fraction.

4. The process design method for improving the strength and plasticity of Al-Mg-Si alloy according to claim 3 is characterized in that: The fraction of the formed solid phase is calculated as follows: In the formula, represents the transition temperature; represents absolute temperature; represents the liquidus temperature; is the equilibrium distribution coefficient of the solute at the solid-liquid interface.

5. The process design method for improving the strength and plasticity of Al-Mg-Si alloy according to claim 1, characterized in that: The driving force for the precipitation of the precipitated phase is calculated as follows: In the formula, is the Boltzmann constant; T is temperature; For the atomic body; It is the liquid phase solute component; is the equilibrium concentration of solute atoms in the matrix.

6. The process design method for improving the strength and plasticity of Al-Mg-Si alloy according to claim 1, characterized in that: The phase change energy barrier is calculated as follows: In the formula, It represents the driving force for the precipitation of the precipitate phase; represents the interface migration rate; is the pre-exponential factor; is the gas constant; is the absolute temperature.

7. The process design method for improving the strength and plasticity of Al-Mg-Si alloy according to claim 1, characterized in that: The Aziz solute retention model in the nonequilibrium solidification process is as follows: In the formula, is the solute retention function; is the interface migration rate; is the solute diffusion rate; is the equilibrium segregation coefficient ratio of solute component A and solvent component B; is the liquid fraction on the moving interface; is the speed of sound in the metal melt; It is the driving force during the solidification of the alloy; is the gas constant; is the interface temperature.

8. Use of the method according to any one of claims 1 to 7 in improving the strength and plasticity of Al-Mg-Si alloy.